REVIEW of the scientific article Yuliia Vyshyvaniuk “Legal Infrastructure for Supporting Small and Medium Businesses in the U.S.” - Kharkivska, Kateryna (Global Prosperity, 2025)
REVIEW of the scientific article Yuliia Vyshyvaniuk “Legal Infrastructure for Supporting Small and Medium Businesses in the U.S.”